Model Layanan PPID Bawaslu dalam Menjamin Hak Penyandang Disabilitas Mengakses Informasi Publik - Maulida Fitria Averoes Averoes; Puji Rianto (Jurnal Mahasiswa Komunikasi Cantrik, 2022)
Access to public information is every citizen’s right. For this purpose, law No. 14/2008 stipulates that any public institution must offer public information services. However, there are no facilities that provide attention and access to disabilities. This study aims to explore the PPID Bawaslu RI service model in ensuring access to public information for persons with disabilities. This research uses the case study technique. The results showed that the PPID Bawaslu RI had enforced the fulfillment of disability information rights. This can be seen from various policies, including; (1) physical or electronic accessibility, consisting of website, email, WhatsApp, SMS, and telephone, although some are still in the optimization process, such as screen readers, glass magnifying features, and keyboard navigation; (2) non-physical accessibility, i.e., assistance to move through the stages of requesting information for the applicant. The effectiveness of the information service model for disabilities has also been applied to the oral and electronic aspects